Effects of Different Pesticide Treatments on Soft Rot Control and Yield of Konjac. Issue 1 (March 2021) - Jiang, Xiong; Wang, Zhengxiang; Yang, Fuqing; Chen, Zhizhou; Yang, Sumian; Yan, Zesheng; Qin, Yaoguo
Abstract: To screen pesticides with improved disease control and increase the yield of konjac plant, we grew one-year-old konjac corms, determined the field control effect, growth indicators, photosynthetic indicators, and yield of konjac plants, and compared the results with those obtained after treatments with three kinds of antibiotic pesticides, three kinds of copper fungicides, chloroisobromine cyanuric acid, bismerthiazol, and water (as control). The results showed that the soft rot incidences in konjac plants after treatment with several pesticides were significantly lower than that of the control (CK). The control effects of tetramycin, copper succinate, and chloroisobromine cyanuric acid were high, the growth status of the plants treated with cuprous oxide, tetramycin, and copper succinate improved; the net photosynthetic rates of each pesticide treatment showed no significant difference from that of the CK, and the yield was the highest with copper succinate and tetramycin. This study demonstrated that certain copper fungicides or antibiotic pesticides can be used for the control of konjac soft rot, but their effects are different. The comprehensive comparison suggests that the effects of copper succinate and tetramycin are the best for the disease control and yield increase of konjac.